Ultrasonographic assessment of the shoulder in patients with carpal tunnel syndrome - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Objectives: To detect the causes of shoulder pain with shoulder ultrasonography in patients with carpal tunnel syndrome (CTS) and compare the findings of the patients with CTS to healthy controls. Patients and Methods: Patients with CTS and healthy controls were evaluated clinically, electrophysiologically. and ultrasonographically by three masked researchers. Electrophysiological assessment consisted median and ulnar nerve conduction studies (NCS). In ultrasonographic assessment, cross-sectional areas of the median nerve were measured at hamatum hook, psiform bone, radio-ulnar joint levels. Shoulder joint, axial and longitudinal biceps tendon, subscapularis tendon, supraspinatus tendon, infraspinatus tendon, rotator cuff, acromioclavicular joint were evaluated by a standardized protocol. Results: The study was completed with 30 patients with CTS and 30 healthy subjects. The presence of shoulder pain in the last week was 53.3% in the CTS group and 30% in the control group but there was no statistically significant difference between the groups (p=0.16; p>0.05). Subdeltoid bursitis was significantly more common in CTS group when compared to the control group (p=0.03) in ultrasonographic assessment, and there was no significant difference between the two groups for other parameters. Conclusion: Shoulder pain and subdeltoid bursitis were common in patients with CTS however, shoulder pain was not directly related to shoulder problems alone. Central sensitization may play a role for shoulder pain rather than shoulder problems.
Keywords: Ultrasonography; Carpal tunnel syndrome; Shoulder pain; Central sensitization